2020
DOI: 10.1093/ehjci/ehaa946.0174
|View full text |Cite
|
Sign up to set email alerts
|

The painful chest pain history: improving risk stratification with coronary calcium score

Abstract: One of the commonest presentations to the Cardiology outpatient clinic is chest pain. Conventional risk scores for predicting coronary artery disease (CAD) depend greatly on chest pain histories which can be subjective and disadvantage individuals who present with less typical symptoms. The coronary calcium score (CACS) has a quick turnabout time and is an objective marker of atherosclerosis which can provide actionable information on presence of coronary artery disease. This study aims to ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…2,3 An abstract our team published demonstrated that chest pain history did not significantly improve coronary artery disease prediction when the calcium score is considered. 4 Additionally, from a standpoint of a specialist chest pain clinic, patients may present with unevaluated risk factors. This causes underestimation of coronary artery disease risk.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 An abstract our team published demonstrated that chest pain history did not significantly improve coronary artery disease prediction when the calcium score is considered. 4 Additionally, from a standpoint of a specialist chest pain clinic, patients may present with unevaluated risk factors. This causes underestimation of coronary artery disease risk.…”
mentioning
confidence: 99%
“… 2 , 3 An abstract our team published demonstrated that chest pain history did not significantly improve coronary artery disease prediction when the calcium score is considered. 4 …”
mentioning
confidence: 99%